siRNA on and off-target - Khvorova, Anastasia (Henry Stewart Talks, 2007)
siRNA target and off-target activity, Systematic analysis of siRNA primary function, Effect of thermodynamic bias on siRNA activity, Development of predictive algorithms for siRNA primary activity, Specific and non-specific siRNA activity, siRNA off-targeting and miRNA mechanism, Bioinformatics in off-target prediction: seed recognition, siRNA off-targeting impact on RNAi applications, siRNA toxicity, siRNA specificity
Reviewed at 2016/01/28